2008
DOI: 10.1111/j.1749-4877.2008.00090.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of gallic acid and propolis on beryllium‐induced hepatorenal toxicity

Abstract: The combined effect of gallic acid (3,4,5-trihydroxy benzoic acid; GA; 50 mg kg -1 i.p.) and propolis (200 mg kg -1 p.o.) was evaluated against beryllium-induced biochemical and morphological alterations in the liver and kidney. Female albino rats were exposed to beryllium nitrate (1 mg kg -1 i.p.) daily for 28 days followed by treatment with the above mentioned therapeutic agents either individually or in combination for five consecutive days. Exposure to beryllium increased its concentration in the serum, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Most interestingly, supplementation of CCl 4 -treated mice with propolis significantly restored the chronic oxidative stress state that was mediated by CCl 4 by increasing the level of GSH and decreasing the level of ROS in the liver tissue lysates. The ability of propolis to reduce oxidative stress and to inhibit free radical formation due to its high content of phenolics [60,61] and the ability of its phenolic compounds to donate hydrogen ions that can attack free radicals to prevent oxidation reactions in the cell [62]. Serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) are reliable markers of liver function, so their levels were estimated.…”
Section: Discussionmentioning
confidence: 99%
“…Most interestingly, supplementation of CCl 4 -treated mice with propolis significantly restored the chronic oxidative stress state that was mediated by CCl 4 by increasing the level of GSH and decreasing the level of ROS in the liver tissue lysates. The ability of propolis to reduce oxidative stress and to inhibit free radical formation due to its high content of phenolics [60,61] and the ability of its phenolic compounds to donate hydrogen ions that can attack free radicals to prevent oxidation reactions in the cell [62]. Serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) are reliable markers of liver function, so their levels were estimated.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors including Nirala et al (2008) and El Sohaimy and Masry (2014) concluded thatpropolis has high a content of phenolics that have the ability to donate hydrogen ions which can attack free radicals to prevent oxidation reactions in the cell.…”
Section: Discussionmentioning
confidence: 99%